1977
DOI: 10.1084/jem.146.6.1534
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of reaginic antibody production in mice. I. Suppression by antigen of IgE antibody production in vitro.

Abstract: Regulation of IgE production by antigen in a primed murine splenic lymphocyte culture system was described. Maximum IgE antibody production was found to occur when cells were cultured in the absence of exogenously added antigen. A cells and T lymphocytes did not affect the production of anti-DNP IgE antibody. By using a hapten-carrier antigen system (DNP-EA) for priming mice in vivo, it was found that the production of anti-DNP IgE by spleen cells in vitro was inhibited by hapten when coupled to homologous (EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Some previous works have indicated [10,22] either that different T and B cells subsets were in volved in the synthesis of IgG and IgE anti bodies, or that IgG and IgE antibody B-forming cells might differ in their reactiv ity versus a same T helper cell. IgE anti body synthesis can be suppressed in vitro or in vivo by antigen-specific or class-specific factors [7,14,19,20]. Indeed, in rats, Tada [20] showed that the IgE response is short lived and hardly boosterable [reviewed by Jarrett,9].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous works have indicated [10,22] either that different T and B cells subsets were in volved in the synthesis of IgG and IgE anti bodies, or that IgG and IgE antibody B-forming cells might differ in their reactiv ity versus a same T helper cell. IgE anti body synthesis can be suppressed in vitro or in vivo by antigen-specific or class-specific factors [7,14,19,20]. Indeed, in rats, Tada [20] showed that the IgE response is short lived and hardly boosterable [reviewed by Jarrett,9].…”
Section: Discussionmentioning
confidence: 99%
“…The cell lysates were separated using a sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), with the isolated protein being transferred onto a polyvinylidene fluoride (PVDF) membrane set to a constant voltage of 80 V. Followed by 1-h of blocking, the membrane was incubated with diluted primary antibodies overnight at 4 °C. The primary antibodies against BMX-ARHGAP and against polyclonal antibody BMX-SH were obtained from the mice immunized as previously described [20]. The primary antibodies used included antibodies for BMX (ab207559, 1:500–1000), ARHGAP (ab74454, 1:500–1000), CD133 (ab216323, 1:1000), CD44 (ab157107, 1:2000), SOX2 (ab92494, 1:1500), JAK2 (ab200783, 1:5000), p-JAK2 (ab32101, 1:2000), STAT3 (ab68153, 1:1500), p-STAT3 (ab76315, 1:2000), Nanog (ab80892, 1:1000) and GAPDH (ab181602, 1:5000).…”
Section: Methodsmentioning
confidence: 99%
“…Danneman and Michael [19]showed that mouse spleen cells obtained 10–11 days after primary immunization with alum–absorbed antigen formed both IgE and IgG antibodies in culture, and that T cells were not involved in antibody formation. In view of the similarities between their findings and our observations, we cultured antigen–primed cells in microtiter plates.…”
Section: Participation Of Long–lived Antibody–forming Cells In Persismentioning
confidence: 99%